Modelling system for short-term forecast of weather and air quality above a city - Starchenko, Alexander V.; Danilkin, Evgeniy A.; Shelmina, Elena A.; Kizhner, Lubov I.; Prokhanov, Sergey A.; Odintsov, Sergey L.; Fazliev, Alexander Z.; Privezentsev, Alexey I.; Svarovsky, Artem I. (Proceedings of SPIE)
For monitoring and short-term forecasting of the meteorological situation and atmospheric air quality near settlements, transport hubs and industrial facilities, the Meteo+ automated computing system is proposed, based on a mathematical model of the atmospheric boundary layer and an effective numerical method focused on the use of supercomputers. The mathematical model includes an impurity transport model with a reduced chemical mechanism and a non-hydrostatic mesoscale meteorological model with a modern moisture microphysics parameterization scheme. Examples of the successful application of the developed automated computing system in the numerical prediction of surface air quality deterioration in light winds and temperature inversions, as well as in the prediction of such dangerous weather phenomena as wind gusts are given.